2016
DOI: 10.1152/ajpcell.00030.2016
|View full text |Cite
|
Sign up to set email alerts
|

Functional and molecular identification of a TASK-1 potassium channel regulating chloride secretion through CFTR channels in the shark rectal gland: implications for cystic fibrosis

Abstract: In the shark rectal gland (SRG), apical chloride secretion through CFTR channels is electrically coupled to a basolateral K conductance whose type and molecular identity are unknown. We performed studies in the perfused SRG with 17 K channel inhibitors to begin this search. Maximal chloride secretion was markedly inhibited by low-perfusate pH, bupivicaine, anandamide, zinc, quinidine, and quinine, consistent with the properties of an acid-sensitive, four-transmembrane, two-pore-domain K channel (4TM-K2P). Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 63 publications
(73 reference statements)
0
6
0
Order By: Relevance
“…They identified the critical role of CFTR as a chaperone for the trafficking of transmembrane ion channels, a mechanism which may equally pertain to other hypoxia-related lung diseases commonly associated with PH, such as COPD or lung fibrosis. In line with the notion that CFTR interacts with other ion channels, the functional complex of TASK-1/CFTR for regulation of chloride secretion in shark rectal gland has been demonstrated [ 231 ].…”
Section: Ion Channels In Pah Pathophysiologymentioning
confidence: 65%
“…They identified the critical role of CFTR as a chaperone for the trafficking of transmembrane ion channels, a mechanism which may equally pertain to other hypoxia-related lung diseases commonly associated with PH, such as COPD or lung fibrosis. In line with the notion that CFTR interacts with other ion channels, the functional complex of TASK-1/CFTR for regulation of chloride secretion in shark rectal gland has been demonstrated [ 231 ].…”
Section: Ion Channels In Pah Pathophysiologymentioning
confidence: 65%
“…The results of the present study demonstrate that multiple K2P channel subtypes are expressed in human mammary epithelial cells and appear to contribute to basal K ϩ secretion. At least four of these subtypes (TREK1, TREK2, TASK1 and TASK3) have been shown to be regulated by different PKC isoforms (21,29,47,52). Additionally, experiments involving BAPTA-AM pretreatment followed by UTP stimulation suggested that Ca 2ϩ -dependent and Ca 2ϩ -independent PKCs were required to produce maximum inhibition of the apical K2P current.…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of total RNA from shark rectal gland tissue, degenerate primer design, PCR, and cloning of PCR fragments. Since the genome of the dogfish shark (Squalus acanthias) is incompletely sequenced, we sought to clone the AMPK␣ gene (PRKAA) in the shark rectal gland by preparing total RNA from rectal gland tissue, and designing degenerate primers for use in PCR reactions, and 5=and 3=-rapid amplification of cDNA ends (RACE) (32). Total RNA was extracted with TRIzol reagents (Invitrogen) from 100 mg of shark tissue that had been excised from the animal and immediately snap frozen in liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…The 3=-and 5=-products were extracted from 2% agarose gels of the RACE-PCR amplifications. These PCR products were then cloned in pCR II TOPO TA cloning vectors (Invitrogen) as previously described (32). Clones were sequenced bidirectionally at the Keck Biotechnology Resource Laboratory at Yale.…”
Section: Methodsmentioning
confidence: 99%